More traditional Dutch ganseys : 65 classic sweaters to knit from 55 fishing villages - Ruhe, Stella (Search Press, 2017)
Between approximately 1875 and 1950, Dutch fishermen wore sweaters with characteristic knit and purl stitch patterns, sometimes cable. These jerseys, known as ganseys, became and intrinsic part of the identity of the Dutchmen who wore them, and their daily lives as fishermen.